Mind Mapping Implementation in Biology Learning (Human Respiration Concept System) to Increase the Activity and Student Learning Outcome - Heriadi Heriadi (Universitas Sebelas Maret, 2015)
Research on activity and student learning outcomes have been made to the students of class XI IPA 2 SMAN 8 Banjarmasin on material human respiratory system. This study aimed to describe the increased activity and student learning outcomes in grade XI IPA 2 SMAN 8 Banjarmasin to human respiratory system materials using cooperative learning model type Mind Mapping. This research method using PTK conducted in two cycles, each cycle consisting of 2 meetings. The results showed that the use of Mind Mapping on the material type of the human respiratory system can increase the student activity seen in the first cycle to the second cycle the student activity makes Mind Mapping as seen from the data obtained in the first cycle by 42% and in the second cycle of 42.05 %. Student learning outcomes such as increased post-test, 60% in the first cycle and the second cycle by 94.15%, The data obtained shows the achievement of classical completeness is set at ≥ 85%. Results LKS nenunjukkan increase of 80.36% in the first cycle and the second cycle amounted to 86.07%, the assessment of character behavior, social skills, processes and psychomotor students during the learning showed excellent category. Based on data from student responses about the type of learning Mind Mapping declare 74.28% strongly agreed, so that learning using cooperative learning model concluded Mind Mapping can increase the activity and learning outcomes of students of class XI IPA 2 SMAN 8 Banjarmasin on the matter of human respiratory system.Keywords: mind mapping, activity, learning outcomes